1998
DOI: 10.1148/radiology.208.1.9646815
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected pulmonary embolism: prospective detection on routine helical CT scans.

Abstract: The prevalence of unsuspected PE was highest among inpatients with cancer. A directed, workstation-based search can improve the PE detection rate over that with hard-copy review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 0 publications
1
76
1
1
Order By: Relevance
“…Up to 1.5% of patients undergoing routine chest CT are found to have an unsuspected PE [15,16]. This incidence increases to 4% in inpatients and 5% in patients with neoplastic disease [16,17]. Wittram [18] suggested that the mean attenuation values for acute and chronic emboli were 78 HU and 87 HU, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 1.5% of patients undergoing routine chest CT are found to have an unsuspected PE [15,16]. This incidence increases to 4% in inpatients and 5% in patients with neoplastic disease [16,17]. Wittram [18] suggested that the mean attenuation values for acute and chronic emboli were 78 HU and 87 HU, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Electron-beam CT and spiral CT have proved reliable in depicting clot (31,32) and the pulmonary vasculature (33), even in patients in whom thromboembolism is not clinically suspected (34,35). In 1997, Mayo et al (36) demonstrated that CT rivaled scintigraphy and Remy-Jardin et al (37) showed that it rivaled conventional angiography in detecting pulmonary thromboembolism.…”
Section: Clinical Applications Thoracic Vasculaturementioning
confidence: 99%
“…Numerosi studi radiologici, sia prospettici sia retrospettivi, hanno valutato la prevalenza di embolia polmonare non sospettata e rilevata incidentalmente in indagini TC di routine [5][6][7]. L'embolia come reperto incidentale è stata riscontrata nell'1,5%-3,4% dei casi, soprattutto nei soggetti di età oltre 60 anni, con una prevalenza ospedaliera dal 4% al 5% e prevalenza ambulatoriale dallo 0,6% al 2,2%.…”
Section: La Prevalenza DI Embolia Polmonare (Ep) Nelle Angio-tc Polmounclassified
“…A number of radiological studies, both prospective and retrospective, assessed the prevalence of pulmonary embolism, previously unsuspected and incidentally detected on routine spiral CT exams [5][6][7]. Unsuspected embolism was found in 1.5%-3.4% of the cases, mainly in subjects over 60 years of age, with an inpatient prevalence of 4% to 5% and an outpatient prevalence of 0.6% to 2.2%.…”
Section: La Prevalenza DI Embolia Polmonare (Ep) Nelle Angio-tc Polmomentioning
confidence: 99%